International Experience in Developing the Financial Resources of Universities - AI-Youbi, Abdulrahman Obaid; Zahed, Adnan Hamza Mohammad; Atalar, Abdullah (Springer Nature, 2021)
This open access book aims to present the experiences and visions of several world university leaders, providing strategies and methods used to find various income sources for their institutions. The expansion of a university system requires a corresponding increase in funding. Consequently, university administrators all over the world are in a constant search for additional funds. If higher-level institutions are expected to deliver high-quality education and research, their sustainable funding is crucial to the development of the countries they serve. While governmental sources are a major part of the funding of most universities, economic downturns as in the case of the COVID-19 crisis may reduce governmental contributions in this and cause administrators to look for various alternative sources to help them compete in a global setting. This book offers valuable information and guidance to university leaders and administrators worldwide especially at a time when university budgets are under stress due to the COVID-19 pandemic with its dire financial and economic consequences.